Automating the Shared Resource Laboratory Using Computer Scripts: A Case Report. Issue 7 (29th April 2019) - Hall, Christopher; Brown, Laura; Graham, Jennifer; Thompson, Sam; Ng, Bee Ling
Abstract: Shared resource laboratories (SRLs) offer instrumentation, training, and support to investigators and play an important role in the progress and development of science. To facilitate daily tasks and to provide an effective service, we have made use of computer scripts; a list of computer commands that are processed sequentially, to automate tasks in our flow cytometry facility. Using Python and an application programming interface (API), we automate user communication and produce a daily schedule display screen. We exploit the accessible nature of open standards to use R and Python to analyze and backup data from the BD Influx cell sorter. Finally, we show that through simple scripting, we can add value to an existing service by producing sort statistics from the Beckman Coulter XDP cell sorter. With these five examples, we demonstrate and wish to inspire other SRLs that the use of scripts helps to improve work efficiency, can solve problems, and can enhance the service provided by the SRL. © 2019 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry.